Constitutional amendment rules : a comparative perspective - Dixon, Rosalind ([Chicago, Illinois] : Law School, University of Chicago, 2011)
"Constitutional amendment rules are now a near universal feature of national constitutions, yet their function remains largely under-theorized. This chapter thus uses a comparative perspective to explore a number of different functions, as well as dangers, to formal procedures for constitutional amendment. It notes, for example, the historical role played by constitutional amendment procedures in Canada, India, South Africa and Australia in: (i) formalizing, or legalizing, major constitutional revisions or changes; (ii) allowing a polity to 'update' of various specific constitutional structures or procedure; and (iii) allowing legislatures to engage in more effective forms of 'dialogue' with courts, by both jump-starting new judicial interpretations of a constitution and trumping existing judicial interpretations. It also explores the dangers of overly flexible amendment, from the perspective of the role of constitutions in promoting valuable forms of political (pre-) commitment, settlement, and minority rights protection. In addition, the chapter concludes by providing a concise summary, and critique, of the existing empirical literature on the actual determinants of the difficulty of constitutional amendment, both cross-nationally as well as within the US."
"May 2011."
Includes bibliographical references.
Title from online title page (viewed March 22, 2013).
Keywords: Constitutional amendments; Constitutional law; Constitutional amendments; Constitutional law